2020
DOI: 10.3389/fonc.2020.599915
|View full text |Cite
|
Sign up to set email alerts
|

How Autophagy Shapes the Tumor Microenvironment in Ovarian Cancer

Abstract: Ovarian cancer (OC) is characterized by a high mortality rate due to the late diagnosis and the elevated metastatic potential. Autophagy, a lysosomal-driven catabolic process, contributes to the macromolecular turnover, cell homeostasis, and survival, and as such, it represents a pathway targetable for anti-cancer therapies. It is now recognized that the vascularization and the cellular composition of the tumor microenvironment influence the development and progression of OC by controlling the availability of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 128 publications
3
31
0
Order By: Relevance
“…Cumulative evidence has reported that ovarian serous carcinoma (OV) has the highest mortality among all histological subtypes of ovarian cancer. As shown in a recent study, we found that the survival data have not changed since 1980 in many areas [ 6 8 ]. Consequently, molecular markers will play an essential role in diagnosing OV at an early stage and assist in the treatment of patients.…”
Section: Introductionsupporting
confidence: 51%
“…Cumulative evidence has reported that ovarian serous carcinoma (OV) has the highest mortality among all histological subtypes of ovarian cancer. As shown in a recent study, we found that the survival data have not changed since 1980 in many areas [ 6 8 ]. Consequently, molecular markers will play an essential role in diagnosing OV at an early stage and assist in the treatment of patients.…”
Section: Introductionsupporting
confidence: 51%
“…It is now accepted that the actual level and functional outcome of autophagy in cancer cells depend on several factors [ 50 ], precisely: (1) the genetic background (i.e., the mutation in relevant oncogenes and tumor suppressor genes as well as in genes controlling the regulatory pathways) of the cancer cell; (2) the presence of growth factors, and the level of inflammation and of secreted inflammatory factors in the TME; (3) the structural and metabolic status of the TME (vascularization, availability of nutrients and of oxygen); and (4) the presence of epigenetic modifiers in the TME. Further, autophagy is a dynamic process that adjusts its regulation in the cells depending on the microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy, a lysosomal catabolic process with homeostatic and pro-survival functions, influences the behavior of ovarian cancer cells, affecting a variety of processes, such as survival in metabolic harsh conditions, invasive growth, the development of immune- and chemo-resistance, the maintenance of stem-like properties and dormancy ( 3 , 11 ). Autophagy is dysregulated in ovarian cancer ( 12 , 13 ), and the autophagy-related proteins BECLIN-1 and LC3 are in fact prognostic factors for ovarian cancer ( 14 - 17 ).…”
Section: Introductionmentioning
confidence: 99%